Airway Foreign Body Mimicking an Endobronchial Tumor Presenting with Pneumothorax in an Adult: A Case Report - Jun-Ho Ha (Medicina, 2021)
Foreign body (FB) aspiration occurs less frequently in adults than in children. Among the complications related to FB aspiration, pneumothorax is rarely reported in adults. Although the majority of FB aspiration cases can be diagnosed easily and accurately by using radiographs and bronchoscopy, some patients are misdiagnosed with endobronchial tumors. We describe a case of airway FB that mimicked an endobronchial tumor presenting with pneumothorax in an adult. A 77-year-old man was referred to our hospital due to pneumothorax and atelectasis of the right upper lobe caused by an endobronchial nodule. A chest tube was immediately inserted to decompress the pneumothorax. Chest computed tomography with contrast revealed an endobronchial nodule that was seen as contrast-enhanced. Flexible bronchoscopy was performed to biopsy the nodule. The bronchoscopy showed a yellow spherical nodule in the right upper lobar bronchus. Rat tooth forceps were used, because the lesion was too slippery to grasp with ellipsoid cup biopsy forceps. The whole nodule was extracted and was confirmed to be a FB, which was determined to be a green pea vegetable. After the procedure, the chest tube was removed, and the patient was discharged without any complications. This case highlights the importance of suspecting a FB as a cause of pneumothorax and presents the possibility of misdiagnosing an aspirated FB as an endobronchial tumor and selecting the appropriate instrument for removing an endobronchial FB.